Penguatan Sistem Dan Prosedur Pinjaman Di Koperasi Saka Tata Makmur Di Kediri Dengan Memanfaatkan Sistem Informasi Manajemen - Lydia Ari Widyarini; Deatri Arumsari Agung; Yulika Rosita Agrippina (LPPM, Universitas Katolik Widya Mandala Surabaya, 2020)
The community service at Saka Tata Makmur Cooperative is important, especially to initiate better changes. The loan system design for the Saka Tata Makmur Cooperative in Kediri can be a good start for the continuation of the organization’s technical and operational activities in the future so that the goals can be achieved, namely the welfare of each member. The design is done by making debtor application SOP, feasibility analysis SOP, credit decision SOP and control and supervision SOP. This activity can be carried out well and dissemination of cooperative management has been done.